2011
DOI: 10.2139/ssrn.2016104
|View full text |Cite
|
Sign up to set email alerts
|

Does Risk Matter? A Semiparametric Model for Educational Choices in the Presence of Uncertainty

Abstract: Standard human capital theory suggests that individuals select into education in order to maximize their utility. If agents are risk averse, they select the educational level that minimizes future uncertainty. The possibility of self-selection complicates the identi cation of the causal contribution of education to uncertainty in future payo s. In this paper the assumption of endogenous school choices due to concerns about future risk is tested and the importance of uncertainty in shaping schooling choices is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In a similar analysis, Kodde () conducted an empirical investigation using a sample of high school students and concluded that the effect of increasing risk (i.e., earnings risk) cannot be signed unambiguously; his empirical results indicated that increasing earnings risk is associated with increased demand for education. More recently, Mazza () found that uncertainty plays an important role in education choices (e.g., academic major) and that individuals generally pursue higher education in an attempt to minimize uncertainty and maximize returns. Fossen and Glocker () found that higher expected returns to education increase the probability of enrollment, while greater uncertainty decreases it.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar analysis, Kodde () conducted an empirical investigation using a sample of high school students and concluded that the effect of increasing risk (i.e., earnings risk) cannot be signed unambiguously; his empirical results indicated that increasing earnings risk is associated with increased demand for education. More recently, Mazza () found that uncertainty plays an important role in education choices (e.g., academic major) and that individuals generally pursue higher education in an attempt to minimize uncertainty and maximize returns. Fossen and Glocker () found that higher expected returns to education increase the probability of enrollment, while greater uncertainty decreases it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choosing whether or not to pursue higher education is risky because consumers do not know with certainty the outcome of future events, including degree completion (Hartog and Diaz‐Serrano ; Mazza ); future labor market supply and demand (Carnevale, Cheah, and Strohl ; Fossen and Glocker ; Kodde ); individual longevity, which affects the duration of earnings realization (Kodde, ); and location in the earnings distribution (Hartog and Diaz‐Serrano ; Kodde ; Levhari and Weiss ; Mazza ). However, there remains a lack of understanding among researchers and policymakers regarding how young adults perceive and handle the risk involved in higher education choices (Dickson and Harmon ).…”
mentioning
confidence: 99%